2011
DOI: 10.1016/j.breast.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age in the outcome and treatment of older women with ductal carcinoma in situ

Abstract: The effect of increasing age on outcomes and type of treatment given to older women with ductal carcinoma in situ (DCIS) was assessed. 646 women ≥60 years old (654 cases) receiving surgery for DCIS at Memorial Sloan-Kettering Cancer Center between 2000 and 2007 (8 bilateral) had wide local excision (WLE; 37%), WLE plus radiotherapy (WLE+RT; 41%), or mastectomy (22%). 45%, 38%, and 16% of patients 60-69 years, 70-79 years, and ≥80 years, respectively, received WLE+RT (P<0.001) and 25%, 20%, and 13%, received ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…34,35 We found no difference in microcalcification morphology or distribution between these two groups. However, younger patients were more likely to have dense breast tissue and multicentric/multifocal disease and undergo mastectomy, while older patients were more likely to present with ER-negative disease.…”
Section: Discussionmentioning
confidence: 48%
“…34,35 We found no difference in microcalcification morphology or distribution between these two groups. However, younger patients were more likely to have dense breast tissue and multicentric/multifocal disease and undergo mastectomy, while older patients were more likely to present with ER-negative disease.…”
Section: Discussionmentioning
confidence: 48%
“…2,5,20,2427 Smith et al 28 found that it contributed to a significant reduction in LRR in women over 65 years old. A more recent study by Ho et al 29 showed no difference in LRR in women over 60 whether or not radiotherapy was used, suggesting that it may be safely eliminated in some older women. This coincides with our findings that young women benefit to a higher degree than older women from radiotherapy after BCS.…”
Section: Discussionmentioning
confidence: 97%
“…In 2017, it is estimated that nearly 53,000 women will be diagnosed with DCIS in the United States . The majority of these women (60%‐77%) will undergo breast‐conserving surgery (BCS), with or without adjuvant therapy . Survival is excellent after BCS for DCIS, with 10‐year breast cancer‐specific mortality rates of 1% to 4% .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The majority of these women (60%-77%) will undergo breast-conserving surgery (BCS), with or without adjuvant therapy. [3][4][5][6] Survival is excellent after BCS for DCIS, with 10-year breast cancer-specific mortality rates of 1% to 4%. [7][8][9][10] However, rates of ipsilateral breast tumor recurrence (IBTR) are not insignificant, with the risk of IBTR reported to be 1% to 3% per year, 5,8 with long-term recurrence rates reported to range from 25% to 35% after BCS alone in 4 large, prospective, randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%